AFFECT DISORDERS AND LIFE QUALITY IN CORONARY HEART DISEASE PATIENTS UNDER DIFFERENT TREATMENT APPROACHES - S. Yu. Mukhtarenko; Т. М. Murataliev; Yu. N. Neklyudova; V. K. Zventsova; А. А. Okunova (Кардиоваскулярная терапия и профилактика)
Aim. To study the prevalence of anxiety-depression symptoms and life quality (LQ) in coronary arteries disease patients (CHD) under a variety of treatment strategies: conservative therapy (CT) and revascularization (MR) — percutaneous intervention (PCI) and coronary bypass (CBG). Material and methods. Totally 106 patients studied with various types of CHD, confirmed with selective coronary arteriography (CAG): 54 (50,91%) of patients underwent CT, 52 (49,06%) underwent MR. All included patients were questioned with the Score by Moscow SRI of Psychiatry. For anxiety and depression disorders we used in-hospital score of anxiety and depression (HADS), Beck depression scale (BDI), Spielberger test for diagnostics of reactive (RA) and personal (PA) anxieties, and for LQ — the Modified Seattle Questionnaire for Angina patients (MSQA). Statistics was done with MS Excel and STATISTICA 6,0 software. Results. By the data of screening questionnaire, in the whole selection of 106 patients with CHD the signs of anxiety-depression disorder (ADD) were marked in 81 (76,48%), were absent in 25 (23,52%) of patients. Higher values of depression by HADS were in the group of CT (7,13±3,58) vs MR (5,73±3,58) (р<0,05), and BDI in the group of CT (16,28±10,55) vs MR (12,0±7,51) (р<0,01). LQ parameter by MSQA was significantly higher in MR group — 27,37±4,44, comparing to CT group — 24,2±5,63 (р<0,001). Mild level of depression by DBI was marked more frequently in CT group comparing to MR group — 46,29% vs 23,08% (р<0,01). Conclusion. By the data of psychometric tests there is higher level of ADD in the group of CT comparing to MR. LQ value by MSQUA in the group of MR (PCI or CBG) was significantly higher in the group of CT.